PENGARUH E-FILING, E-BILLING, E-FAKTUR DAN E-SPT TERHADAP KEPATUHAN PAJAK PADA BMT DI KOTA MALANG - Muhammad Wildan; Abdul Wahid Mahsuni; Siti Aminah Anwar (e_Jurnal Ilmiah Riset Akuntansi, 2022)
This study aims to understand the impact of e-filing, e-billing, e-invoicing, and e-SPT on tax compliance at Baitul Maal Wattamwil in Malang City. This type of study is explanatory research using primary data. The population in this study is Baitul Maal Wattamwil in Malang City, which is 39 BMTs. Determination of the sample using the saturated sampling method is the method of determining the sample if the entire population is used as a sample. In this study, the sample is the Manager at Baitul Maal Wattamwil in Malang City. The data analysis method used is multiple linear regression analysis through the help of SPSS 20. Based on the results of the study that has been completed, it shows that simultaneously e-filing, e-billing, e-invoicing, and e-SPT on tax compliance at Baitul Maal Wattamwil in Malang City. Partial testing shows that all variables affect tax compliance at Baitul Maal Wattamwil in Malang City. Keywords: e-filing, e-billing, e-invoicing, e-SPT and tax compliance.